Sosial Media Sebagai Strategi Untuk Meningkatkan Branding Kelompok Tani Maju 01 - Taufik Rizal Dwi Adi Nugroho; Aulia Kafi Yugi Shah; Era Vanessa Noer (Jumat Informatika: Jurnal Pengabdian Masyarakat, 2024)
The Farmer Group "Tani Maju 01" in Junggo Hamlet plans to form a modern farmer group that can compete in the global era. This service aims to increase the existence of Poktan Tani Maju 01 through social media, especially Instagram so that it becomes better known among the public. The method used is a discussion method which begins with a discussion with members of the farmer group to obtain an understanding of resolving the problems that occur. The service was carried out by helping to create an Instagram account during a regular once a month meeting on October 1 2023 at Mr Paeri's house. The Poktan Tani Maju 01 Instagram account with the username @poktan_tanimaju01 was distributed to members during a regular meeting on October 31 2023 at Mr Bayu Wijanarko's house. Instagram poktan Tani Maju 01 is used as a medium for publicizing activities carried out by members of the farmer group as well as branding the farmer group so that it is known to the wider community.